Investment Trends Among Young Generation: Exploring Motivation and Educational Influence of Gen Z and Millennials - Fitria Dewi; Herni Herni; Rina Destiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze how motivation and education affect investment interest among the younger generation, especially Generation Z and Millennials, which shows a dominance trend in capital market investment activities in Indonesia. With economic growth and the rapid development of digital technology, the younger generation now has wider and easier access to applicable information and investment instruments. This study utilizes a quantitative method with a population consisting of students of Gunung Jati Swadaya University Cirebon. Data was obtained through a questionnaire distributed to 157 respondents and analyzed using SmartPLS 3.0. The results of the analysis show that investment motivation and education have a positive and significant influence on investment interest. This suggests that the higher the level of motivation and education an individual receives, the greater their inclination to invest in the capital market. The implications of this study show the importance of providing inclusive and adaptive financial education to the characteristics of the younger generation. This research also provides strategic input for financial industry players and the government in designing future education programs that are able to arouse the interest and participation of the younger generation in the capital market. However, the limitations of this study include the narrow scope of respondents and approaches that do not capture changes in long-term dynamics, so further and in-depth follow-up research is needed.